Penyuluhan Kesehatan Mengenai Pemanfaatan Tanaman Obat Keluarga (TOGA) untuk Kesehatan di Desa Gunung Salak - Anak Agung Ngurah Putra Riana Prasetya; Ni Luh Putu Silvia Andaresta; I Gusti Ayu Putu Priyanti; Ni Ketut Kristina Dewi; Adinda Amalia; Ni Kadek Ayu Widhyanti; Ni Luh Putu Damayanti; Ni Luh Sukma Widiastuti (Unika Santu Paulus Ruteng, 2022)
The utilization of family medicinal plant or known as TOGA has been used as a medication since ancient time. Until now, the scientific use of TOGA has not been widely known by the Indonesian people, one of which is the community in Gunung Salak Village, Tabanan, Bali. Some people in Gunung Salak village are known to have cultivated several types of TOGA, but the majority of the people there don’t know yet the function and how to use TOGA for health. Health education activities regarding the use of TOGA are carried out with the aim of increasing public knowledge, especially Banjar Kemetug and Banjar Apit Yeh, as well as increasing responses from village officials to support efforts to cultivate and utilize TOGA scientifically and massively. The provision of questionnaires to the people in both Banjar as evaluation material for this health education activity. Statistical analysis was carried ot on each item of the questionnaire questions and the understanding of each respondent who had filled out the questionnaire, both before and after the extension using Mc Nemar test. The majority of respondents who attended were aged 41-50 years (40%) and had a high level of understanding related to TOGA both before (76%) and after health education (100%). Based on Mc Nemar analysis, it was found that there was a significant difference of each respondent who had filled out the questionnaire before and after the health education (p=0,004). Overall there was a significant difference of each question item on the questionnaire (p<0,05). This indicates that the extension activity that has been carried out can increase the understanding of the community in Gunung Salak Village and increase efforts to cultivate and use TOGA